Sharks for the Aquarium and Considerations for Their Selection - Alexis L. Morris; Elisa J. Livengood; Frank A. Chapman (EDIS)
Sharks are magnificent animals and an exciting group of fishes. And they are becoming increasingly popular as pet animals. The proper care and display of sharks requires great attention to details. This 7-page fact sheet provides critical points aquarists must consider in deciding whether or not to include sharks in their aquaria. A table of the most popular sharks kept in public and home aquariums is provided to facilitate species selection. Written by Alexis L. Morris, Elisa J. Livengood, and Frank A. Chapman, and published by the UF Department of School of Forest Resources and Conservation Program in Fisheries and Aquatic Sciences, December 2010.